Production of heparin and λ-carrageenan anti-heparanase derivatives using a combination of physicochemical depolymerization and glycol splitting. (15th June 2017) - Poupard, Nicolas; Groult, Hugo; Bodin, Justine; Bridiau, Nicolas; Bordenave-Juchereau, Stéphanie; Sannier, Frédéric; Piot, Jean-Marie; Fruitier-Arnaudin, Ingrid; Maugard, Thierry
Highlights: Ultrasonic-assisted radical depolymerization gave LMW-λ-Carrageenan. Depolymerization associated with glycol splitting helped modulate biological activities. Lead to interesting heparanase inhibitors with low-anticoagulant properties. RD-GS-λ-Carrageenan most interesting candidate as potent antiangiogenic. Same heparanase inhibition as UF-heparin but with no anticoagulant properties. Abstract: Strongly associated with tumor angiogenesis and metastasis, the enzyme heparanase is an endo-β-d -glucuronidase which is overexpressed in the tumor microenvironment. Its inhibition could be one of the most promising anti-angiogenic approaches to date. Although heparin is known as a good heparanase inhibitor, it also possesses major anticoagulant properties that may be incompatible with its use as an anti-angiogenic agent, hence the considerable interest for other sources of sulfated polysaccharides. Recent investigations point to λ-carrageenans, highly sulfated galactans with a tremendous potential that are found in red algae. This study describes the production of low-molecular-weight (LMW) heparins and λ-carrageenans, using a combination of glycol splitting and ultrasonically-assisted radical hydrolysis using hydrogen-peroxide. The structural characteristics, as well as the anticoagulant and antiheparanase activities of the resulting products were assessed. The best candidate was a LMW glycol-split λ-carrageenan that displayed major anti-heparanase properties, with an IC50 of 7.32 ng/mL and a close-to-zero anticoagulant activity.